Arbitration in Africa under OHADA Rules - Vital Kodo, Mahutodji Jimmy (Wolters Kluwer Law International, 2020)
Arbitration in Africa under OHADA Rules' is the first-ever publication in English on the topic globally. Over recent decades, African countries have witnessed an increase in international investment, which has led to the need for a harmonized legal environment across borders creating, inter alia, a modern arbitration system. The 1993 Treaty establishing the Organization for the Harmonization of Business Law in Africa (OHADA) took a giant step toward meeting this need and improved and consolidated its achievements with major arbitration-related revisions enacted in 2017 that came into force in 2018. This book, the first systematic analysis in English, elucidates in detail the ad hoc and institutional arbitration regimes that characterize the system. It aims to keep the practitioners abreast of all that they need to know to conduct arbitral proceedings efficiently in any of the Ohada's seventeen Member States.